A Formal Model for Context-Awareness - Kjærgaard, Mikkel Baun; Bunde-Pedersen, Jonathan (BRICS Report Series, 2006)
There is a definite lack of formal support for modeling real- istic context-awareness in pervasive computing applications. The Conawa calculus presented in this paper provides mechanisms for modeling complex and interwoven sets of context-information by extending ambient calculus with new constructs and capabilities. In connection with the calculus we present four scenarios which are used to evaluate Conawa. The calculus is a step in the direction of making formal methods applicable in the area of pervasive computing.